Analysis of the Performance of the mBJLDA Potential Considering Pressure Effects. (Análisis del rendimiento del potencial mBJLDA considerando efectos de presion.) (2015)
AbstractIn this paper a detailed analysis of the performance of the modified Becke-Johnson potential (mBJLDA) considering hydrostatic pressure effects is reported. The band gap was calculated for a set of semiconductors using the mBJLDA potential. These results were compared with those obtained by other methods of calculation, in order to have an objective judgement of this potential. It was found that the GW approximation (GWA) gives the most accurate predictions. The mBJLDA potential is slightly less precise, in general. The hybrid functionals are less accurate, on the overall. In 88% of the semiconductors considered the error was less than 10%. Both, the GWA and the mBJLDA potential, reproduce the band gap of 15 of the 27 semiconductors considered with a 5% error or less. Next, the behavior the mBJLDA potential was analyzed to describe the hydrostatic pressure effects. The pressure coefficients were calculated and also the volume deformation potential for a set of semiconductors using this potential. The calculated values correlate quite well with other theoretical reports. With these results, it was concluded that the mBJLDA potential performs reasonable well in describing the hydrostatic pressure effects on the band gap of semiconductors. ResumenEn este artículo se presenta un análisis detallado del rendimiento del potencial modificado de Becke-Johnson (mBJLDA), considerando los efectos de la presión hidrostática. La brecha de energía prohibida fue calculada para un grupo de semiconductores usando el potencial mBJLDA. Estos resultados se compararon con los obtenidos por otros métodos de cálculo, para lograr un juicio objetivo de este potencial. Se encontró que la aproximación GW (GWA) brinda las predicciones más precisas. El potencial mBJLDA es, en general, un poco menos exacto. Los funcionales híbridos son menos precisos. En el 88% de los semiconductores tenidos en cuentra, el error fue menor del 10%. Tanto GWA como el potencial mBJLDA reproducen la brecha de energía prohibida de 15 de los 27 semiconductores considerados, con un error del 5% o menor.Enseguida, se analizó el comportamiento del potencial mBJLDA para describir los efectos de la presión hidrostática. Se calcularon los coeficientes de presión y el potencial de deformación volumetrica para un grupo de semiconductores utilizando este potencial. Los valores calculados se correlacionan muy bien con otros informes teóricos. Con estos resultados se concluyó que el potencial mBJLDA opera razonablemente bien en la descripción de los efectos de la presión hidrostática sobre la brecha de energía prohibida de los semiconductores.